Cytoplasmic male sterility in plants with special emphasis on sugar beet - Sadzik, Gabriela (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
The phenomenon of cytoplasmic male sterility (CMS) in plants is characterized by a disturbance in the development of functional pollen. The cause of this disorder is the incompatibility of the mitochondrial and nuclear genome. Determinants of CMS are found in the mitochondrial genome and are inherited maternally. Nuclear Rf genes are responsible for restoring male fertility in CMS plants most often by posttranscriptional and/or posttranslational activity on mitochondrial gene expression. Two fertility restoring genes have been identified in sugar beet plants, of which Rf1 is the best characterized. It is concluded that the translation product of this gene acts as a molecular chaperone leading to inactivation of a specific mitochondrial protein that is a marker for the CMS trait in sugar beet. The CMS phenomenon is applied in the commercial breeding of hybrid varieties of many crop species. Exploiting heterosis is easier with the knowledge of cytoplasmic (mitochondrial) determinants of sterility and corresponding restorer genes.